Effect of co-culture with Halomonas mongoliensis on Dunaliella salina growth and phenol degradation - Zhang, Jinli; Huang, Bo; Tang, Tao (Frontiers in Bioengineering and Biotechnology, 2022)
The discharge of industrial phenol wastewater has caused great harm to the environment. This study aims to construct microalgae and bacteria co-culture system to remove phenol from simulated high-salt phenol wastewater and accumulate microalgae biomass. The degradation of phenol by marine microalgae Dunaliella salina (D. salina) and phenol-degrading bacteria Halomonas mongoliensis (H. mongoliensis) was investigated preliminarily, and then the effects of co-culture H. mongoliensis and D. salina on the degradation of phenol and the growth of D. salina were studied. The effects of D. salina/H. mongoliensis inoculation ratio, light intensity, temperature and pH on the performance of the co-culture system were systematically evaluated and optimized. The optimal conditions for phenol degradation were as follows: a D. salina/H. mongoliensis inoculation ratio of 2:1, a light intensity of 120 μmol m−2 s−1, a temperature of 25°C and a pH around 7.5. Under optimal conditions, this co-culture system could completely degrade 400 mg L−1 of phenol within 5 days. Correspondingly, the phenol degradation rate of D. salina monoculture was only 30.3% ± 1.3% within 5 days. Meanwhile, the maximum biomass concentration of D. salina in coculture was 1.7 times compared to the monoculture. This study suggested that this coculture system had great potential for the bioremediation of phenol contaminants and accumulate microalgae biomass.